Hindenburg power, myth, and the rise of the Nazis - Von der Goltz, Anna, 1978- (Oxford historical monographs., 2009)
'Hindenburg' reveals how a previously little-known general whose career to normal retirement age had provided no real foretaste of his heroic status, became a national icon and living myth in Germany after the First World War, capturing the imagination of millions.